STRATEGI PEMERINTAH TERHADAP PEMBERDAYAAN PEREMPUAN BERBASIS WIRAUSAHA DESA CIPOTAKARI - Ratna Dewi; Erfina Erfina; Monalisa Ibrahim; Sahar Sahar (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
The purpose of this study is to determine the government's strategy for empowering women based on entrepreneurship in Cipotakari village, to determine the factors that influence the government's strategy to empower women based on entrepreneurship in Cipotakari village. The population of this study was 280 people (adult women), while the research sample was 72 people. The data collection techniques used in this study were (1) observation, (2) literature study, and (3) questionnaire. The collected data was then analyzed using a frequency table and using the SPSS 2.1 application. The results of the research on the Government's Strategy for the Empowerment of Entrepreneur-Free Women in Cipotakari Village, Panca Rijang District, can be categorized as "not good" with a percentage of 50% based on the results of respondents' recapitulation on government strategy indicators. The factors that influence the leadership of the village head in empowering women from the percentage results have an influence of 2.3%, while the power factor on the Cipotakari village government in giving authority to women to become entrepreneurs from the percentage results has an influence of 0%. This can be seen from the t test, where t count 0.960 is smaller than t table 1.997, so H0 is accepted meaning that it is not significant. So the Government's Strategy has no significant effect on Entrepreneurial-Based Women's Empowerment in Cipotakari Village.